Study of thermal conductivity of light concrete based on rice husks - DOKO, KOUANDETÉ VALERY (My University, 2013)
Rice production generates waste after decortications. These rice husks which, if they are not used for energy, they provide a space for the environment and therefore can be used in the manufacture of composite materials. This study deals with the determination of the thermal conductivity of composite cement-rice husk, rice husk-sand-cement and sand-cement method ‘’ comparison’’ based on the principle of guarded hot plate. Composites studied exhibit the following physical characteristics: composite 1, rice husk cement, has a density of 901.17 ± 30.11kg/m3, a poros ity of 31.22 ±0.25% and a thermal c onductivity of 0.638 ± 0.061 W / m K, while the c ompos ite 2, sand-cement has a density of 2220.00± 73.33kg/m3, a porosity of 8.61 ± 0.22% and a conductivity Thermal 1.30± 0.27 W / m K. In view of the results, rice husk composites have better thermal performance because we have a reduction of the thermal conductivity of about 50% compared to the sand-cement composite.
Keywords: rice husks; agricultural waste; porosity; density; thermal performance; hygroscopic.